2019
DOI: 10.3390/atmos10100589
|View full text |Cite
|
Sign up to set email alerts
|

Solar UV Radiation in Saint-Denis, La Réunion and Cape Town, South Africa: 10 years Climatology and Human Exposure Assessment at Altitude

Abstract: Solar ultraviolet radiation (UVR) monitoring is important since it depends on several atmospheric parameters which are associated with climate change and since excess solar UVR exposure and has significant impacts on human health and wellbeing. The objective of this study was to investigate the trends in solar UVR during a decade (2009–2018) in Saint-Denis, Reunion Island (20.9°S, 55.5°E, 85 m ASL) and Cape Town, South Africa (33.97°S, 18.6°E, 42 m ASL). This comparison was done using total daily erythema expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…e dose required to produce sunburn is dependent on skin type; 2 SED is likely to elicit erythema in a very sensitive skin type (Fitzpatrick skin type I), whereas higher skin types (Fitzpatrick skin type V or VI) may require 20 SED to develop erythema [19,50].…”
Section: Data Collection Erythema Effective Uv (Uv Ery ) Dosementioning
confidence: 99%
“…e dose required to produce sunburn is dependent on skin type; 2 SED is likely to elicit erythema in a very sensitive skin type (Fitzpatrick skin type I), whereas higher skin types (Fitzpatrick skin type V or VI) may require 20 SED to develop erythema [19,50].…”
Section: Data Collection Erythema Effective Uv (Uv Ery ) Dosementioning
confidence: 99%
“…When going through the atmosphere, UVR is subject to several amplitude variations. Surface UVR is modulated by several parameters: atmospheric parameters such as ozone, aerosols, or clouds [3][4][5]; geographic parameters (such as latitude or altitude); temporal parameters (seasons or time of the day, i.e., solar zenith angle [6]).…”
Section: Introductionmentioning
confidence: 99%
“…Sea level climatological averages showed that the UVI can reach 8 during winter and 16 during summer on Reunion Island [24,25]. Reunion is a mountainous island where Cadet et al [6] reported a maximum UVI of 20 at~2900 m height. However, the UVI is not well known by the local population and there is even a low awareness of the extreme UVI dangers by the local dermatologists [26].…”
Section: Introductionmentioning
confidence: 99%
“…The cloud cover can be important, but the UVR can be maximal if the sun is not hidden by clouds. The UVR can also be increased in the case of scattered cloud cover [10,41].…”
Section: Clear Sky Filteringmentioning
confidence: 99%
“…Reunion Island (55 • E, 21 • S) is a tropical island situated in the Western Indian Ocean (Figure 1) and is exposed to extreme UVR all year around. UVI is generally in the range of 0 to 16 and can exceed 20 under certain conditions, such as at high altitude or cloud diffusion [10]. Therefore, UVI measurement, public awareness, and prevention campaigns are very important for Reunion Island and in tropical regions in general.…”
Section: Introductionmentioning
confidence: 99%